IMPLEMENTASI KERJA SAMA ANTARA INDONESIA DENGAN KOREA SELATAN DALAM JOINT WORKING GROUP ON HEALTH PASCA PANDEMI COVID-19 - Alman, Putri Raina; Renolafitri, Hendrini; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The COVID-19 pandemic underscored health as a non-traditional security issue that directly affects national stability, particularly for Indonesia, which continues to face limitations in health infrastructure and vaccine production capacity. In contrast, South Korea demonstrated stronger crisis management due to adaptive public health strategies and a well-developed biopharmaceutical industry. These differing capacities prompted the strengthening of bilateral cooperation through the Joint Working Group (JWG) on Health in the post-pandemic period. This study aims to examine the implementation of Indonesia–South Korea cooperation under the JWG on Health and identify the factors shaping it. The analysis draws on neoliberalism, Robert O. Keohane’s theory of international cooperation, Budi Winarno’s concept of non-traditional security, and Kenneth Waltz’s levels of analysis. Methodologically, the study applies a qualitative approach using literature-based research guided by Mestika Zed, encompassing academic works, official documents, and international reports. The findings reveal that the JWG on Health has been realized through the establishment of a plasma fractionation facility, joint research initiatives, biopharmaceutical technology transfer, and hospital-to-hospital collaboration. At the individual level, leadership from the Minister of Health and biopharmaceutical industry figures plays a significant role. At the state level, Indonesia focuses on strengthening national health resilience, while South Korea advances pharmaceutical industry expansion and health diplomacy. At the international system level, the pandemic heightened global health interdependence and underscored the need for sustained institutional cooperation. Overall, this collaboration serves as a strategic effort to enhance health resilience, advance health diplomacy, and deepen long-term bilateral ties in the post-pandemic era. Keywords: International cooperation, JWG on Health, Indonesia – South Korea, Neoliberalism, Non-traditional security.